The Role of immune and inflammatory mechanisms in ALS - McCombe, P A; Henderson, R D (Current molecular medicine, 2011)
Amyotrophic lateral sclerosis (ALS) is a severe progressive neurodegenerative disease. The cause is unknown, but genetic abnormalities have been identified in subjects with familial ALS and also in subjects with sporadic ALS. Environmental factors such as occupational exposure have been shown to be risk factors for the development of ALS. Patients differ in their clinical features and differ in the clinical course of disease. Immune abnormalities have been found in the central nervous system by pathological studies and also in the blood and CSF of subjects with ALS. Inflammation and immune abnormalities are also found in animals with a model of ALS due to mutations in the SOD1 gene. Previously it has been considered that immune abnormalities might contribute to the pathogenesis of disease. However more recently it has become apparent that an immune response can occur as a response to damage to the nervous system and this can be protective.